Using the Merdeka Curriculum for English Language Instruction - Balqis, Sarah Lidya; Rohbiah, Tatu Siti; Rahmawati, Eulis (SCOPE: Journal of English Language Teaching, 2025)
This research explores the application of the Merdeka Curriculum to the teaching of English at SMAN 1 Cilegon and SMAN 2 Krakatau Steel Cilegon. Using a qualitative descriptive method proposed by Creswell, the study investigates teaching planning, material development, instructional strategies, and student achievement. Data obtained through observation and in- depth interview. The findings reveal essential aspects of the implementation: Firstly, teachers meticulously design lesson plans based on differentiated learning principles. They thoroughly understand Learning Outcomes (CP), formulate corresponding Learning Objectives (TP), and create Learning Objectives Flows (ATP) to establish a logical teaching sequence. This planning aims to create an inclusive and effective learning environment catering to diverse student needs. Secondly, English teaching materials in the Merdeka Curriculum emphasize varied content, including the use of technology and the internet as crucial information sources. Active student engagement is encouraged through diverse media, and teachers adapt strategies for complex materials. Additionally, teachers customize learning materials and employ strategies like Jigsaw and project-based learning to meet students' diverse needs. Both schools prioritize initial and final assessments to gauge prior knowledge and track progress, promoting tailored teaching. Finally, students in both schools show progress, notably in speaking and writing skills, with the Merdeka curriculum. The inclusion of project-based learning, specifically the P5 project, distinguishes the Merdeka curriculum and captivates students. This research has implications about practical Merdeka Curriculum implementation in English instruction, offering guidance for teachers and institutions in optimizing the curriculum for diverse student populations.